(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
A biostratigraphic study was carried out on four sections of the Miocene Tufillo and Faeto Formations (Southern Apennines). The sediments analyzed were referred to the late Burdigalian-early Tortonian on the basis of planktonic foraminifers (MMi2b Subzone through the MMi8 Zone) and calcareous nannofossils (MNN3b Zone through the MNN7 Zone). Almost the majority of the bioevents of the recently published Miocene biozonal schemes of Mediterranean area were identified. Particularly, the marked changes in the abundance pattern of Paragloborotalia siakensis resulted very useful to correlate the sediments. A new acme abundance of the letter species has been recorded in the uppermost part of the Burdigalian planktonic foraminiferal MMi2b Subzone. Moreover, the integrated calcareous plankton biostratigraphy revealed that the First Common Occurrence (FCO) of Sphenolitus heteromorphus occurs before the Last Occurrence (LO) of Catapsidrax dissimilis, in the upper part of Burdigalian record. This study indicates that the lower Langhian portion of the Tufillo Formation is characterized by arkose sandstones which pass upwards into calcarenites and/or calcirudites and marly deposits. Field data suggest that these sandstones directly overly the "Numidian Sandstones". The Faeto Formation starts with calcarenites and calcareous marls, in the calcareous nannofossil MNN3b Zone (Burdigalian), and lies on the "Numidian Sandstones" as well. High-resolution sampling and biostratigraphy reveal that the deposition of the "Numidian Sandstones" ends in the late Burdigalian stage, just below the FCO of S. heteromorphus (MNN3b Zone) and the LO of C. dissimilis (MMi2b Subzone).